Hierarchically Porous Multilayered Carbon Barriers for High‐Performance Li–S Batteries. Issue 15 (19th February 2018) - Chang, Zhi; Ding, Bing; Dou, Hui; Wang, Jie; Xu, Guiyin; Zhang, Xiaogang
Abstract: As one of the most promising energy storage devices, the practical application of lithium–sulfur batteries is limited by the low electrical conductivity of sulfur and the notable "shuttle effects" of sulfur‐based electrodes. In this work, we describe a hierarchically porous N‐doped zeolitic imidazolate framework‐8 (ZIF‐8)‐derived carbon nanosphere (N‐ZDC) with an outer shell and an inner honeycomb‐like interconnected nanosheet network as sulfur host material for high‐performance and long‐term lithium–sulfur batteries. The N‐ZDC serves as multilayered barrier against the dissolution of lithium polysulfides. The porously inner interconnected carbon network of the N‐ZDC facilitates the electron and ion transportation, ensures a high sulfur loading, and accommodates a volume expansion of the sulfur species. As a result, the optimized N‐ZDC 4 /S electrodes displayed high initial specific capacities of 1343, 1182, and 698 mAh g −1 at 0.5, 1, and 2 C, respectively, and an ultraslow capacity decay of only 0.048 % per cycle at 2 C over 800 cycles. Even with a high sulfur loading of 3.1 mg cm −2, N‐ZDC 4 /S still delivered a reversible capacity of 956 mAh g −1 and stabilizes at 544 mAh g −1 after 500 cycles at 0.5 C, revealing the great potential of the novel carbon nanospheres for energy storage application. Abstract : Shuttle break : Hierarchically porous N‐doped carbon (N‐ZDC) spheres with an outer shell and an inner interconnected carbon network act as multilayered barrier to effectively suppress the dissolution of lithium polysulfides and enhance the active material utilization, thus improving the cycling performance of Li–S batteries.